Nonlinear Optical Materials of Inorganic−Organic Hybrid Semiconductors (R− C6H4CHCH3NH3)2PbI4 (Texas Journal of Multidisciplinary Studies, 2024)
This study presents the synthesis, crystal structure, and optical properties of two-dimensional (2D) layered inorganic-organic (IO) hybrid semiconductors, namely (R-C6H4C2H4NH3)2PbI4, where R can be either CH3 or Cl. These compounds exhibit a natural self-assembly.Synthesis of the nonlinear optical materialls of Inorganic−Organic Hybrid Semiconductors of (Cl-C6H4-C2H4-NH3)2PbI4 with PbJ4 salt, study of its composition and structure by physical research methods. (RNH3) + moieties sandwiched between two infinite 2D layers of the [PbI6] 4- octahedral network, resembling IO multiple quantum wells. The CH3 compound crystallizes in an orthorhombic system in the Cmc21 space group, while the Cl compound crystallizes in a monoclinic system in the P21/c space group. When fabricated as thin films, both compounds exhibit good orientation along the (100) direction. Single crystals and thin films of these compounds display strong Mott-type exciton features at room temperature, which are highly influenced by the self-assembly and crystal packing. The confined excitons, residing within the lowest band gap of the inorganic material, exhibit distinct photoluminescence peaks under one- and two-photon excitation. The perfectly aligned 2D self-assembly generates free excitons, while the locally crumpled layered arrangement leads to energy downshifted excitons.